Journeying together: A visual exploration of "engagement" as a journey in HIV programming and service delivery. (January 2020) - Switzer, Sarah; Flicker, Sarah; McClelland, Alexander; Chan Carusone, Soo; Ferguson, Tatiana B.; Herelle, Neil; Yee, Derek; Guta, Adrian; Strike, Carol
Abstract: The experiences of people living with, or impacted by HIV, who participate in research and programming are relatively-well documented. However, how stakeholders within the HIV sector understand engagement, or how it functions discursively, is undertheorized. We used a comparative case study design and photovoice to explore engagement in three community-based organizations providing HIV programs or services in Toronto, Canada. We invited stakeholders to photograph their subjective understandings of engagement. We employ a visual and thematic analysis of our findings, by focusing on participants' use of journey metaphors to discuss engagement within and across sites. Visual metaphors of journey were employed by participants to make sense of their experience, and demonstrated that for many, engagement was a dynamic, affective and relational process. Our findings illustrate how journey may be an apt metaphor to explore the relational, contingent and socio-spatial/political specificities of engagement within and across HIV organizations. We conclude with a discussion on implications for practice. Highlights: Understandings of engagement vary within and across the HIV sector in Toronto, Canada. Journey is an apt metaphor to discuss these different understandings in HIV organizations. Journey metaphors show that engagement is a dynamic and relational process. Understandings of engagement are shaped by organizational context(s) and roles.